2021
DOI: 10.1021/acsaelm.1c00556
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Role of Substrates on Domain Distribution of Quasi-2D Perovskites for Blue Light-Emitting Diodes

Abstract: Perovskite light-emitting diodes (PeLEDs) have been developed at a rapid pace with high external quantum efficiencies (EQEs) surpassing 20% for red, infrared, and green emissions; nevertheless, the performance of their blue-emitting cousins remains relatively quite low. Among various crucial factors that could impact these solution-processed devices, selection of a suitable underlayer (usually a hole-transport layer) is critical to the quality of resulting perovskite films. Particularly, the role of the substr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Another approach to controlling the distribution of the 2D and 3D phases in the films is proper selection of the underlying layer. PEDOT:PSS, poly[(9,9-dioctylfluorenyl-2,7diyl)-co-(4,4-(N-(4-sec-butylphenyl)diphenylamine)] (TFB), poly(9-vinylcarbazole) (PVK), and poly[bis(4-phenyl)(4-butylphenyl)amine] (poly-TPD) have been used as HTLs in LED device architectures [69][70][71][72]. Moreover, most of the MHP layers were directly deposited on the PEDOT:PSS layer through solution processing.…”
Section: Phase Engineeringmentioning
confidence: 99%
See 2 more Smart Citations
“…Another approach to controlling the distribution of the 2D and 3D phases in the films is proper selection of the underlying layer. PEDOT:PSS, poly[(9,9-dioctylfluorenyl-2,7diyl)-co-(4,4-(N-(4-sec-butylphenyl)diphenylamine)] (TFB), poly(9-vinylcarbazole) (PVK), and poly[bis(4-phenyl)(4-butylphenyl)amine] (poly-TPD) have been used as HTLs in LED device architectures [69][70][71][72]. Moreover, most of the MHP layers were directly deposited on the PEDOT:PSS layer through solution processing.…”
Section: Phase Engineeringmentioning
confidence: 99%
“…Moreover, most of the MHP layers were directly deposited on the PEDOT:PSS layer through solution processing. Therefore, the crystallization kinetics of MHP crystal growth during solution processing was significantly affected by the underlying layer [69,70]. Cai et al reported that when TFB was used as the HTL, lower-dimensional 2D phases (2 ≤ n ≤ 4) were formed more favorably than when PE-DOT:PSS was used as the HTL [69].…”
Section: Phase Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly, the hole mobility is higher than the electron mobility in such layered perovskite films. , For instance, Ahn et al introduced polyvinylpyrrolidone (PVP) as an insulating layer to lower the hole-current and achieve better charge-carrier balance, which resulted in Q-2D green PeLEDs with improved performance . Notably, the electron mobility of commonly used electron transport material 2,2′,2″-(1,3,5-benzinetriyl)-tris­(1-phenyl-1- H -benzimidazole) (TPBi) is only 3.3 × 10 –5 cm 2 V –1 s –1 , which is much inferior to the mobility of the widely used hole transport material poly­[(9,9-dioctylfluorenyl-2,7-diyl)- alt -(4,4′-( N -(4-butylphenyl)] (TFB); this difference in electron–hole mobilities consequently exacerbates the imbalance between electron and hole currents in the device. , Such imbalanced charge injection in PeLEDs results in the formation and accumulation of excitons at the perovskite/ETL interface, which can be quenched by the cathode or be transformed to joule heat, thereby contributing to the low efficiency with severe roll-off and operational instability. Moreover, the interfaces between EML and the charge transporting layers are vulnerable to various defects that further deteriorate the performance of PeLEDs.…”
Section: Introductionmentioning
confidence: 99%